The Influence of Muhammad Abduh in Indonesia - Ahmad Nabil Amir; Tasnim Abdul Rahman (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2021)
Muhammad Abduh had a remarkably profound and lasting impact in Indonesia. His reformist ideas had a strong repercussion in the political and social landscape of the region. They were readily adopted by major Islamic movements, notably Muhammadiyah, al-Irshad and Persatuan Islam (Persis). Abduh’s Tafsir al-Manar deeply influenced some momentous works of Qur’anic exegesis, such as Tafsir al-Azhar, Tafsir al-Qur’an al-Karim, Tafsir al-Qur’an al-Madjid (Tafsir al-Nur), Tafsir al-Misbah and Tafsir al-Furqan. His Majallat al-Manar, which was planned and collaborated with Rashid Rida since 1898, highly inspired reform-oriented scholarship evident in journals such as al-Munir, and al-Dhakhirah al-Islamiyah. This study aims to analyze the influence of Abduh’s modernism in Indonesia. It attempts to discover the implication of his principle and philosophical tradition in the religious reform and modern movement in Indonesia. The method of study is based on qualitative approaches, using content analysis method. It was conducted based on library method to investigate the related data from primary and secondary sources. The data was analyzed using descriptive-analytical approaches, by way of inference (istisqa’) and deductive (istinbat) method. The paper concluded that Abduh had profound and extensive influence in the Archipelago, especially his impact on Islamic reform and renewal (islah and tajdid) in Indonesia.